Dietary supplements compendium (United States Pharmacopeial Convention, 2009)
Developed for manufacturers, contract laboratories, and distributors, this reference contains the DSHEA standards and information needed to develop, manufacture, and test quality dietary supplement products.
Includes index.
Keywords: Dietary supplements industry.; Dietary supplements.; elektronické knihy; electronic books